Comprehending and measuring pandemic induced stress among professionals due to lockdown and work from home. (15th November 2021) - Srivastava, Richa; Gupta, Srikant; Sanjeev, M. A.
Abstract : Covid‐19, a once‐in‐a‐century pandemic, has caused a great deal of anxiety worldwide. In addition to the apparent virus‐induced morbidity and mortality, pandemic‐induced stress has contributed to the lack of human wellbeing during Covid‐19. Most efforts have gone into understanding the physical effects and less on the pandemic's mental effects. The new normal of social distancing and work‐from‐home (WFH), requiring disconcerting home confinement levels, has been a prime cause of stress. The pandemic‐induced stress encompasses infection‐related suffering, economic and professional loss, social isolation caused by lockdowns, information‐induced anxiety, need to integrate work and life—from earlier balancing them, and stress‐induced by sudden changes in the routine. The study's primary objective is to develop and validate a scale to measure lockdown and WFH‐induced stress among professionals in employment. The result indicates three significant stressors: job stress, social stress, and routine stress affecting professionals due to lockdown and WFH. The study results would help employers, and healthcare professionals measure the lockdown and WFH‐induced stress among working professionals, which is a prerequisite for managing the same through appropriate interventions.